2020
DOI: 10.1097/md.0000000000019371
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal medicine for premature ovarian insufficiency

Abstract: Background: Premature ovarian insufficiency (POI) is the loss of function of the ovaries before age 40. Chinese herbal medicine (CHM) has been treating POI for long time. Therefore, we conduct this study to assess the efficacy and safety of CHM for POI. Methods: Seven databases will be searched from inception to December 31, 2018: PubMed, Embase, Cochrane Library, Chinese National Knowledge Infrastructure (CNKI), China Biology Medicine disc (CBM), WanFa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As a result, numerous patients are switching to complementary and alternate medicine (CAM). As one major branch of CAM, traditional Chinese medicine (TCM), regarded as having less side effects, has been extensively used in China and in other countries to treat ovarian aging [106][107][108]. According TCM theory, ovarian aging diseases i are related to kidney, liver, spleen, heart, lung and other zang-organs' mulfunction(we need to declare specifically that in the TCM theory, "kidney, liver, spleen, heart, lung"are not as same as the cencepts of morden medicine), espectially uterus mulfunction; dysregulation of thorough fare and conception vessels is the key link of ovarian aging pathogenesis.The etiology and pathogenesis concludes cold evil invasion, qi and blood deficiency, liver stagnation and qi stagnation, phlegm and blood stasis block, which eventually lead to meridian block, stagnation of qi and blood activities, zang-fu dysfunction.…”
Section: The Role Of Traditional Chinese Medicinementioning
confidence: 99%
“…As a result, numerous patients are switching to complementary and alternate medicine (CAM). As one major branch of CAM, traditional Chinese medicine (TCM), regarded as having less side effects, has been extensively used in China and in other countries to treat ovarian aging [106][107][108]. According TCM theory, ovarian aging diseases i are related to kidney, liver, spleen, heart, lung and other zang-organs' mulfunction(we need to declare specifically that in the TCM theory, "kidney, liver, spleen, heart, lung"are not as same as the cencepts of morden medicine), espectially uterus mulfunction; dysregulation of thorough fare and conception vessels is the key link of ovarian aging pathogenesis.The etiology and pathogenesis concludes cold evil invasion, qi and blood deficiency, liver stagnation and qi stagnation, phlegm and blood stasis block, which eventually lead to meridian block, stagnation of qi and blood activities, zang-fu dysfunction.…”
Section: The Role Of Traditional Chinese Medicinementioning
confidence: 99%
“…Herbal medicine is one of the most common forms of traditional Chinese medicine (TCM) and has always been considered the best among the treatment methods in Chinese medicine. Studies have shown that CHM is effective in treating POF [ 28 ]. There are numerous reports in the Chinese literature about the treatment of POF with herbal remedies, but only abstracts are available in English.…”
Section: Herbal Remediesmentioning
confidence: 99%
“…Herbal medicine is one of the most common forms of traditional Chinese medicine (TCM) and has always been considered the best among the treatment methods in Chinese medicine. Studies have shown that CHM is effective in treating POF [28].…”
Section: Herbal Remediesmentioning
confidence: 99%